Occupational health and safety risk assessment in hospitals: A case study using two-stage fuzzy multi-criteria approach - Gul, Muhammet; Ak, M. Fatih; Guneri, Ali Fuat (TAYLOR & FRANCIS INC, 2017)
Occupational Health and Safety (OHS) is a basis to reduce occupational accidents in an acceptable level, and it covers employee health, safety, and welfare in the workplaces. Hospitals as the largest employer group in healthcare industry in Turkey face major hazards categorized as chemical, biological, physical, ergonomic, and psychosocial risks. Although Turkey demonstrates rapid economic growth, OHS practices have not been fully put into practice, and necessary attention has not been paid to the health industry. For this reason, this paper aims to assess risks for health staff, contribute for planning of health services, and enhance regulations. A case study was carried out in a leading hospital in Turkey using a two-stage fuzzy multi-criteria approach, which provides more consistency in decision-making process and gives an appropriate final rank of hazard types. Fuzzy Analytic Hierarchy Process (FAHP) is used in weighing five risk parameters, which are severity, occurrence, undetectability, sensitivity to maintenance non-execution, and sensitivity to personal protective equipment (PPE) non-utilization. The fuzzy VIKOR (FVIKOR) approach is then applied for prioritization of hazard types in each department of the hospital. On conclusion of the hazard control hierarchy, measures are overtaken for the hazards, and areas open for improvement are presented.
Keywords: occupational health and safety; risk assessment; hospitals; FAHP; FVIKOR; FAILURE MODE; DECISION; VIKOR; HAZARDS; FMEA; Biodiversity & Conservation; Environmental Sciences & Ecology